Anti-N-methyl-D-Aspartate Receptor Encephalitis Mimicking Sporadic Creutzfeldt–Jakob Disease - Liu, Jiao; Chen, Liyan; Yang, Jing; Wang, Lan; Shang, Huifang; Chen, Xueping (Frontiers in Neurology, 2020)
Objectives: Anti-NMDAR (N-methyl-D-aspartate receptor, NMDAR) encephalitis and sporadic Creutzfeldt-Jakob disease (sCJD), share similar clinical features. Here, we present two unusual cases of anti-NMDAR encephalitis who were misdiagnosed as sCJD at first. Methods: We described two patients’ clinical manifestations, as well as the string of symptomatological evolution, treatments, and follow-up results. Results: Our patients presented with rapid progressive dementia, memory problems, psychiatric symptoms, and movement disorders, and we considered all these symptoms as a presenting feature of sCJD at first, but the cerebrospinal fluid (CSF) examination showed positive results for both the 14-3-3 protein and antibodies against NMDAR. Immunomodulatory treatment led to a resolution of these deficits, and both of them remained in remission after treatment. Conclusion: Anti-NMDAR encephalitis can present with rapid progressive cognitive decline, and sometimes laboratory investigations can be misleading. The examination for the presence of NMDAR antibodies is necessary, even with the presence of 14-3-3 protein. Early immunomodulatory therapy should be considered, especially for patients with high titers of NMDAR antibodies.